The Affect of Delivery Security and Service Features on Customer Satisfaction Wahana Express - Yana Tatiana; Sesaria Mardhiani Rachma Puspita; Lintang Eka Cahya Samudra; Agung Putra Anugrah (Jurnal Ilmu Multidisiplin, 2025)
This research examines how delivery security and service features influence customer satisfaction with Wahana Express. In the digital era, the quality and reliability of logistics services are critical for enhancing customer satisfaction. Using quantitative methods, data were collected via questionnaires distributed to Wahana Express customers. The analysis reveals that delivery security significantly impacts customer satisfaction, followed by the service features offered. These findings suggest that logistics companies should focus on improving security and enriching service features to enhance customer satisfaction and remain competitive in the market.